Pengaruh Bauran Pemasaran Terhadap Keputusan Konsumen Menggunakan Jasa Hotel King Ameer Toili: The Effect of Marketing Mix on Consumer Decisions to Use Hotel Services King Ameer Toili - I Wayan Fery Arta; Melda Gienardy; Wiwin Anggriani Salawali (Jurnal Ilmiah Produktif, 2022)
This research was conducted to analyze the variables of the influence of the marketing mix on consumer decisions to use the services of the King Ameer Toili Hotel. The research conducted by researchers at the King Ameer Hotel Toili, Toili District is a qualitative descriptive study that has been quantified so that in the scoring category using a Likert scale, the analytical tool uses Multiple Linear Regression. Correlation Coefficient, Coefficient of Determination, T-Test and F-Test. Data collection techniques in this study were using questionnaires and interviews. The results of the research and discussion described above show that the Marketing Mix variable which consists of product, price, place, promotion, people, process, and physical evidence simultaneously has a significant effect on consumer decisions to use the services of Hotel King Ameer Toili. The results of data processing for Multiple Linear Regression using the Multiple Linear Regression equation as follows: Y = 2.083 + 0.169X1 + 0.288X2 + 0.201X3 + 0.060X4 + 0.065X5 + 0.046X6 + 0.199X7 + e. The coefficient of determination (R2) is 186. The results of the F test show the value of Fcount 3.898 and Ftable 2.21 (Fcount > Ftable) = 3.898 > 2.21 with a Sig F level of 0.001 < 0.05, then H0 is rejected and Ha is accepted. By using a sample of 90 respondents with df = n – k – 1 = 90 – 7 – 1 = 82. Then Ttable is 1.664 with a significance level (α) of 0.05.